The Use of Prophylaxis Antibiotics to Prevent Acute Pancreatitis Complications: Meta-Analysis of Clinical Trials - Dwita Nitoya Esterini; Kirsten Putriani Hartman; Joue Abraham Trixie; Yessi Setianegari; Kurniyanto Kurniyanto (The Indonesian Society for Digestive Endoscopy, 2021)
Background: Acute pancreatitis (AP) is an inflammation of the pancreas, a serious emergency with no definitive treatment. It may progress to infected necrosis, non-pancreatitis infection, also death that may occur within the first 1 to 2 weeks. The use of prophylactic antibiotics in AP to prevent complications remains a controversy. The objective of this meta-analysis is to assess the benefit of prophylaxis antibiotics administration to prevent the complication.Method: Trials were identified by searching the medical database. Literature range is within the year 1975 to 2021. Review Manager 5.4.1 was used to analyse data extraction and risk of bias of included studies were elaborated. Risk ratio (RR) was calculated with 95% confidence interval (CI). P 0.05 was considered significant.Results: Twenty trials with a total of 1.287 patients of AP were analysed; 646 patients treated with antibiotic prophylaxis and 641 patients treated with placebo. Prophylaxis antibiotics were found to have significant difference between the two groups. The administration of prophylaxis antibiotics lower the risk of non-pancreatic infections (RR = 0.77; 95% CI: 0.62–0.95; p 0.05) and infected pancreatic necrosis (RR = 0.74; 95% CI: 0.58-0.94; p 0.05). Meanwhile, prophylaxis antibiotics were found to be insignificant to lower the risk of mortality (RR = 0.75; 95% CI: 0.54-1.03; p 0.05). Conclusion: Prophylaxis antibiotics lower the risk of non-pancreatic infections and infected pancreatic necrosis, but did not lower the risk of mortality.